2013
DOI: 10.1080/03601234.2013.781372
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of advanced wastewater treatment plant system and laboratory-scale micelle-clay filtration for the removal of ibuprofen residues

Abstract: The efficiency of Al-Quds Waste Water Treatment Plant (WWTP), which includes sequential elements as activated sludge, ultrafiltration, activated carbon column and reverse osmosis, to remove spiked ibuprofen, a non steroid anti inflammatory drug (NSAID), was investigated. Kinetic studies in pure water and in the activated sludge indicated that the drug was stable during one month of observation. Besides, the overall performance of the integrated plant showed complete removal of ibuprofen from wastewater. Activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…[30,30,[34][35][36]47] Khamis et al [30] concluded that the incorporation of micelle-clay filters in sewage treatment systems with lose of tertiary capability can be a promising technology. In a recent paper, Karaman et al [31] showed that micelle-clay filters were more efficient towards removal of diclofenac from wastewater than activated carbon.…”
Section: Filtration Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30,30,[34][35][36]47] Khamis et al [30] concluded that the incorporation of micelle-clay filters in sewage treatment systems with lose of tertiary capability can be a promising technology. In a recent paper, Karaman et al [31] showed that micelle-clay filters were more efficient towards removal of diclofenac from wastewater than activated carbon.…”
Section: Filtration Resultsmentioning
confidence: 99%
“…More recently, Khalaf et al [47] suggested that the integration of clay-micelle complex filters in existing WWTPs may be helpful for improving removal efficiency of recalcitrant residues of non-steroid anti-inflammatory drugs.…”
Section: Drugmentioning
confidence: 99%
“…It has been shown by X-ray diffraction, electron microscopy, and adsorption experiments that the material characteristics of the micelle-clay complex are different from those of an organo-clay complex, which is formed by adsorption of the same organic cations ODTMA as monomers [28]. Micelle-clay composites have already been proven to be efficient in the removal of about 20 neutral and anionic pollutants [18,[21][22][23][24][25][26][27]31,32].…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…The obtained complex by virtue of its positive charge and hydrophobic region is capable of efficiently binding neutral and negatively charged organic molecules [18,[21][22][23][24]28]. …”
Section: Micelle-clay Complex Preparationmentioning
confidence: 99%
See 1 more Smart Citation